Blockade of cholesterol absorption by ezetimibe reveals a complex homeostatic network in enterocytes - Luke J. Engelking; Matthew R. McFarlane; Christina K. Li; Guosheng Liang (Journal of Lipid Research, 2012)
Enterocyte cholesterol homeostasis reflects aggregated rates of sterol synthesis, efflux, and uptake from plasma and gut lumen. Cholesterol synthesis and LDL uptake are coordinately regulated by sterol regulatory element-binding proteins (SREBP), whereas sterol efflux is regulated by liver X receptors (LXR). How these processes are coordinately regulated in enterocytes, the site of cholesterol absorption, is not well understood. Here, we treat mice with ezetimibe to investigate the effect of blocking cholesterol absorption on intestinal SREBPs, LXRs, and their effectors. Ezetimibe increased nuclear SREBP-2 8-fold. HMG-CoA reductase (HMGR) and LDL receptor (LDLR) mRNA levels increased less than 3-fold, whereas their protein levels increased 30- and 10-fold, respectively. Expression of inducible degrader of LDLR (IDOL), an LXR-regulated gene that degrades LDLRs, was reduced 50% by ezetimibe. Coadministration of ezetimibe with the LXR agonist T0901317 abolished the reduction in IDOL and prevented the increase in LDLR protein. Ezetimibe-stimulated LDLR expression was independent of proprotein convertase subtilisin/kexin type 9 (PSCK9), a protein that degrades LDLRs. To maintain cholesterol homeostasis in the face of ezetimibe, enterocytes boost LDL uptake by increasing LDLR number, and they boost sterol synthesis by increasing HMGR and other cholesterologenic genes. These studies reveal a hitherto undescribed homeostatic network in enterocytes triggered by blockade of cholesterol absorption.